The SK™ external fixation system: description of components, instrumentation, and application techniques - Toombs, J. P.; Bronson, D. G.; Ross, D.; Welch, R. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The SK™ external fixator was designed to overcome the problems commonly encountered with clinical use of the Kirschner-Ehmer (KE) splint. It enables the use of a range of different fixation pin diameters within a construct, improved pin centering within the bone, increased flexibility in frame construction and disassembly, and a decreased need for the use of full-pins to achieve fracture stabilization. The SK™ external fixator is available in three sizes: mini, small, and large. This report describes the components of the SK™ ESF system, the instrumentation needed to apply it, and the recommended application techniques.
Keywords: SK™ external fixation components